Effect of cooked rice with added fructo-oligosaccharide on faecal microorganisms investigated by in vitro digestion and fermentation - Fei Pei; Wen Li; Xiaolei Ni; Xinyang Sun; Yijun Yao; Yong Fang; Wenjian Yang; Qiuhui Hu (Food Science and Human Wellness)
In the present study, the effects of cooked rice (CR) with added fructo-oligosaccharide (FOS) on faecal flora were studied by a simulated in vitro digestion and fermentation method. The total carbohydrate content, pH, and short-chain fatty acids (SCFAs) were determined during in vitro digestion and fermentation. The change in the bacterial phase distribution after the fermentation was also analysed. The results showed that the total carbohydrate content of the CR with added FOS (FCR) significantly decreased during the simulated digestion. Meanwhile, the pH of the FCR decreased and the SCFAs concentration increased significantly compared to those of the CR during the simulated fermentation. In addition, the FCR showed the advantage of promoting beneficial bacteria, such as Bifidobacterium and Lactobacillus, and inhibiting harmful bacteria, such as Bacteroides and Klebsiella compared to the CR. Therefore, the FOS as a prebiotic could be recommended to produce the high-quality healthy rice food.